Termos de parentesco nas línguas Tuparí (família Tupí) - Nogueira, Antônia Fernanda Souza (Museu Paraense Emílio Goeldi, 2025)
This article analyzes and compares the kinship terms in the five languages ​​of the Tuparí branch, establishes the general patterns of the terminology of the kinship system, and proposes the reconstruction of the main kinship terms for the ancestral language of the current languages, Proto-Tupari. Based on the comparison of the kinship terminologies of the Tuparí languages ​​and the correlates reconstructed for Proto-Tupari, we present here an analysis of the terminological patterns of the kinship systems of the Tuparí groups, seeking to identify their main characteristics, through a comparative approach internally to the Tuparí branch and in relation to the main classifications of the kinship systems of the Amazonian groups, especially the Tupí groups.